2021
DOI: 10.3390/biomedicines9121896
|View full text |Cite
|
Sign up to set email alerts
|

Lactotransferrin Downregulation Serves as a Potential Predictor for the Therapeutic Effectiveness of mTOR Inhibitors in the Metastatic Clear Cell Renal Cell Carcinoma without PTEN Mutation

Abstract: Approximately 30% of clear cell renal cell carcinoma (ccRCC) patients develop metastatic spread at the first diagnosis. Therefore, identifying a useful biomarker to predict ccRCC metastasis or therapeutic effectiveness in ccRCC patients is urgently needed. Previously, we demonstrated that lactotransferrin (LTF) downregulation enhanced the metastatic potential of ccRCC. Here, we show that LTF expression conversely associates with the mTORC1 activity as simulated by gene set enrichment analysis (GSEA). Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Local recurrence and distant metastasis remained major obstacles to the clinical treatment of NPC. EMT has become a key process of cell invasion and metastasis in most epithelial tumors (including NPC) [24,25]. Recent studies have shown that a large number of genetic or epigenomic changes and genetic instability jointly control NPC occurrence, which is a complex process involving the interaction regulation of numerous molecular networks [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local recurrence and distant metastasis remained major obstacles to the clinical treatment of NPC. EMT has become a key process of cell invasion and metastasis in most epithelial tumors (including NPC) [24,25]. Recent studies have shown that a large number of genetic or epigenomic changes and genetic instability jointly control NPC occurrence, which is a complex process involving the interaction regulation of numerous molecular networks [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt/mTOR pathway is one of the main downstream signal transduction pathways of LTF, and LTF exerts anticancer effects in various cancers by influencing the PI3K/Akt/mTOR pathway [24,25]. Thus, it is reasonable to speculate that the change in NPC cell phenotype caused by LTF may be due to the regulation of the PI3K/AKT/mTOR pathway.…”
Section: The Influences Of Ltf On Npc Cell Metastasis and Emt Are Par...mentioning
confidence: 99%
“…Notably, studies have revealed that the down-regulation of lactotransferrin, a significant protein in the innate immune system, promotes metastasis in ccRCC. Interestingly, this down-regulation also renders the ccRCC tumor cells more responsive to mTOR inhibitors, suggesting its potential as a predictor for therapeutic effectiveness (22).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…It has been suggested in some reports that the LTF can regulate cell growth, migration, and invasion in several cancers 13 . For example, previous studies have found that LTF is associated with proliferation, migration, invasion and promoted apoptosis of clear cell renal cell carcinoma 14 , 15 . LTF has also been suggested to downregulate the development of nasopharyngeal carcinoma by inhibiting the proliferation through induction of cell cycle arrest and modulation of the MAPK signaling pathway 16 .…”
Section: Introductionmentioning
confidence: 99%